PENGARUH MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS III - Roni Hamdani, Acep; Putri Ayu, Puput (STKIP Subang, 2020)
This study aims to determine the effect of generative learning models to improve the mathematical connections of elementary school students. This research was conducted at SDN Tanjungwangi in the academic year 2020/2021 with a research sample of 20 class III A students and 20 class III B students. This research method uses a quasi-experimental method. The data analysis technique in this study uses the N-gain calculation to measure the increase in the ability of students 'mathematical connections, (t-test) to determine the effect of using generative learning models on students' mathematical connection abilities. The results showed that (1) there was an increase in the mathematical connection ability with an average N-gain in the experimental class, the result was 0.79 with the